Mechanisms of Action of Propofol in Modulating Microglial Activation in Ischemic Stroke - Pouria Abdolmohammadi; Bashir Bietar; Juan Zhou; Christian Lehmann (Molecules)
Ischemic stroke, responsible for the majority of stroke cases worldwide, triggers profound neuroinflammatory responses largely mediated by microglia. Excessive activation of pro-inflammatory microglia exacerbates neuronal injury, highlighting the need for therapeutic strategies targeting microglial modulation. Propofol (2,6-diisopropylphenol), a widely used intravenous anesthetic, has emerged as a promising neuroprotective agent due to its potent anti-inflammatory properties. This review comprehensively explores the diverse cellular mechanisms by which propofol attenuates microglial activation and inflammation in ischemic stroke. By elucidating these molecular pathways, it underscores the therapeutic potential of propofol in mitigating ischemic brain injury and guiding future clinical interventions.